PENGARUH METODE BERNYANYI TETRHADAP PERKEMBANGAN BAHASA ANAK USIA DINI DI LEMBAGA RA RABBANI ISLAMIC SCHOOL - Khairunnisa Khairunnisa (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Language is a great tool. With language we can express our thoughts and feelings towards other people. Language can be expressed in various forms, namely speech, writing and gestures. The human organs that play a role are the mouth and throat. Language can also exist without speaking, for example a person is mute - deaf because he cannot hear oral expressions and language so he cannot speak. Seeing the differences in each child, there are three important things that teachers must pay attention to in developing children's language skills to average, namely the number of vocabulary they should master, clarity in speech, and speech disorders. Language is very important to use for socializing, so language needs to be developed from an early age. Learning through the singing method on children's language development may be more effective. Because singing is a fun activity that is loved by children. The singing method is a learning method that uses chanted lyrics. Singing makes the learning atmosphere cheerful and passionate so that children's language development can be stimulated optimally. In addition, singing may increase vocabulary so that children's language development can develop optimally.